2009
DOI: 10.1007/s00464-009-0755-1
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of emergent vs. elective hospital admissions for an intrathoracic stomach

Abstract: Strikingly, more than half of admissions for intrathoracic stomach were emergent. Emergent admissions had higher mortality, longer LOS, and higher cost than elective admissions. These data support consideration of early elective repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 11 publications
1
26
0
4
Order By: Relevance
“…We recently reported an audit of the New York Statewide Planning and Research Cooperative System administrative database including nearly 5,000 admissions for an intrathoracic stomach over 5 years (2002)(2003)(2004)(2005)(2006). 17 With or without surgical intervention, emergent admissions had a higher mortality, longer length of stay, and higher hospital costs when compared to elective admissions. When assessing admissions with operative repair only, emergent operative admissions had nearly 5-fold higher mortality (5.1% vs. 1.1%) and doubled length of stay and hospital costs compared to elective operative admissions.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported an audit of the New York Statewide Planning and Research Cooperative System administrative database including nearly 5,000 admissions for an intrathoracic stomach over 5 years (2002)(2003)(2004)(2005)(2006). 17 With or without surgical intervention, emergent admissions had a higher mortality, longer length of stay, and higher hospital costs when compared to elective admissions. When assessing admissions with operative repair only, emergent operative admissions had nearly 5-fold higher mortality (5.1% vs. 1.1%) and doubled length of stay and hospital costs compared to elective operative admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were demonstrated by Ponsky et al 16 All of our patients underwent complete esophageal mobilization and sac excision, but our study did not demonstrate any significant difference in recurrence rates between patients who did or did not undergo gastropexy (P = .21). doplication, cruroplasty, and posterior onlay of a polyester mesh (Parietex; Covidien) if a hiatus with a surface area of 5.60 cm 2 or greater was present. The authors reported no significant complications with the use of mesh and concluded that recurrence was more likely with increased hiatal surface area.…”
Section: Research Original Investigationmentioning
confidence: 99%
“…Operative repair is recommended to treat associated symptoms and conditions such as gastroesophageal reflux disease (GERD), postprandial shortness of breath, gastric outlet obstruction, postprandial pain, erosive esophagitis or Cameron's erosions that may result in anemia, and to prevent subsequent enlargement of the hernia and a more challenging repair in the future [7,8,9,10]. Early repair is also recommended to prevent gastric volvulus or strangulation, as emergent PEH repair is associated with a 5-20 times increase in morbidity and mortality compared to elective repair [11]. …”
Section: Discussionmentioning
confidence: 99%